ANALISIS PENGAWASAN KUALITAS PRODUK DENGAN METODE STATISTICAL PROCESSING CONTROL PADA PERCETAKAN KELUD JAYA CILACAP - Herni Utami Rahmawati; Krishna Santosa Yusat; Niken Febianti (Majalah Imiah Manajemen & Bisnis, 2021)
The purpose of this research is to analyze the deviation of the proportion of damaged products produced by books during the last five years against the predetermined standards, as well as to analyze the quality of goods produced in accordance with the requirements set by the company. The sampling technique used was non-random sampling. The analysis tools are the Z Test and the Control Chart Method. The results of this study indicate that the proportion of damaged products produced by books during the last five years has not deviated from the standards set by the company; The quality of the products manufactured by the company is in accordance with established requirements. The implication of the results of this research is that Kelud Jaya Cilacap Printing needs to improve company policies to reduce the number of product defects as small as possible with tighter quality control in order to produce quality products. Keywords : Supervision; Quality; product